Electrophoretic Codeposition of MoOx/MoS2 Thin Film for Platinum-Free Counter Electrode in Quantum Dot Solar Cells - Thanh Tung Nguyen; Huy Phap Ngo; Van Thang Le; Le Thanh Nguyen Huynh; Viet Hai Le; Thai Hoang Nguyen; Hoang Long Ngo (International Journal of Photoenergy)
The MoOx/MoS2 thin films were manufactured on conducting glass (FTO) from the ethanolic mixture of colloidal molybdenum disulfide (MoS2) and molybdenum oxides (MoOx) by electrophoretic deposition method and were used for counter electrode of quantum dot solar cells. Different ramp-rate conditions for electrophoretic deposition as well as bias potential were investigated in an attempt to get the highest possible electrocatalytic activity of polysulfide (S2-/Sn2-) redox couple. In this research, interestingly, by simply using CdS/CdSe/ZnS photoanode and polysulfide electrolyte under 1000 W.m−2 AM 1.5 G illumination, the power conversion efficiency of MoOx/MoS2-counter-electrode-based QDSC was achieved up to 2.01%, which was double compared to platinum-based counter electrode of QDSCs.